Pengaruh Kosentrasi Pencampuran Tepung Bonggol Pisang Termodifikasi untuk Pembuatan Mie Basah - Azizah, An Nisa Luthfi Nur; Hamid, Hamid (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Banana tuber flour is a type of non-wheat flour which has a high carbohydrate content so it has the potential to be processed into noodles. However, due to the low protein content and immature physicochemical properties, it is necessary to modify it enzymatically and mix it with wheat flour to obtain good quality noodles. This study aims to obtain enzymatically modified banana tuber flour with suitable characteristics for application in the manufacture of wet noodle products, as well as to obtain a formula (comparison of modified banana tuber flour and wheat flour) which can produce wet noodles that meet the SNI quality requirements. The treatment tested was enzymatically modified banana tuber flour substitution 10%, 20%, 30%, 40% and 0% were used as control variables. Wet noodle products were tested for water content and noodle organoleptic (smell, color and texture) according to SNI 2987:2015 wet noodle quality requirements. The results showed that the level of wet noodles met SNI standards, namely below 65%. The organoleptic test results showed that the best quality wet noodles were obtained from a combination of 10% modified banana tuber flour and 90% wheat flour with a concentration ratio of -amylase enzyme of 10%. The aroma test obtained a combination of 10% modified banana tuber flour and 90% wheat flour with a concentration ratio of -amylase enzyme of 40%.